Vocational Teachers Readiness in Integration The Principles of Industrial Revolution 4.0 into The Learning Process - Muhammad Amin; Bima Mustaqim (Elinvo (Electronics, Informatics, and Vocational Education), 2021)
The Indonesian government has started to fix the problem of industrial change with 'Making Indonesia 4.0' as a strategy to pave the way for Indonesia to become one of the new powers in Asia. One of the steps taken is to change the education system in Vocational High Schools in Indonesia where the education system has turned into competency-based and student-oriented education since April 2018. Teachers must be highly qualified in order to produce students capable of meeting the challenges of the industry revolution 4.0. In this article, we ask the following: "What is the level of teacher readiness in integrating the principles of the industrial revolution 4.0 in the learning process?". Furthermore, this research employs a quantitative technique because data collection this study uses research instruments and its presentation is related to numbers which aim to describe the phenomenon that occurs, including teacher readiness. According to our results, Vocational High School teachers are in the category of ready to integrate the principles of industrial revolution 4.0 in the learning process which is seen from several aspects, follows: (1) Education Competence (EC), (2) Competence for Technological Commercialization (CTC), (3) Competence in Globalization (CG), 4) Competence in Future Strategies (CFS), (5) Counselor Competence (CC). The rapid development of technology can make it easier for vocational teachers to dig up information about industrial revolution 4.0. Therefore that vocational teachers are in the ready category to integrate the principles of the industrial revolution 4.0 in the learning process.